COVID-19 Crisis: How Can Plant Biotechnology Help? - Shohag, Md. Jahidul Islam (Plants (Basel), 2021)
The emergence of the COVID-19 pandemic has led to significant public health crisis all over the world. The rapid spreading nature and high mortality rate of COVID-19 places a huge pressure on scientists to develop effective diagnostics and therapeutics to control the pandemic. Some scientists working on plant biotechnology together with commercial enterprises for the emergency manufacturing of diagnostics and therapeutics have aimed to fulfill the rapid demand for SARS-CoV-2 protein antigen and antibody through a rapid, scalable technology known as transient/stable expression in plants. Plant biotechnology using transient/stable expression offers a rapid solution to address this crisis through the production of low-cost diagnostics, antiviral drugs, immunotherapy, and vaccines. Transient/stable expression technology for manufacturing plant-based biopharmaceuticals is already established at commercial scale. Here, current opinions regarding how plant biotechnology can help fight against COVID-19 through the production of low-cost diagnostics and therapeutics are discussed.